ANALYZE OF THE ROMANIAN'S AGRICULTURE ESPECIALLY IN THE POST EU ACCESSION PERIOD - Nagy, Szeréna (Acta Carolus Robertus, 2021)
Agriculture is a vital activity that plays a key role in the food security of the population and has a great impact on the regional and local ecosystems, becoming a strategic tool for the economic development of any country.The role and the importance of the agriculture sector in the national economy has declined in most countries, but on the other hand the role of agriculture in Romania and other countries cannot be circumvented nowadays.The purpose of the study is to analyze, identify the place and the role of agriculture in Romania's actual economy from the perspective of GDP, the employment of this sector activity, because Romanian agriculture remains an important sector in terms of view of agricultural area used, the contribution to GDP and, in particular, the percentage of the rural population employed.
Keywords: Agriculture sector; productivity; GDP; employment, land use